DETECTION OF INFECTIOUS MYONECROSIS VIRUS (IMNV) IN LITOPENAEUS VANNAMEI USING NESTED REVERSE TRANSCRIPTION-POLYMERASE CHAIN REACTION (PCR) AT PT. CENTRAL PROTEINA PRIMA SIDOARJO EAST JAVA - Nur Amalliyah, Hanifah; Hakimah, Nisa; Sugianti, Budi (Jurnal Perikanan Unram, 2025)
Increased production and stocking density have elevated the risk of viral diseases, which can lead to significant economic losses. This study aimed to detect the presence of Infectious Myonecrosis Virus (IMNV) in vannamei shrimp using the Nested Reverse Transcription-Polymerase Chain Reaction (nRT-PCR) method. 54 vannamei shrimp samples from various regions in Indonesia were tested to detect the presence of IMNV. The test results showed 2 samples were detected positive for IMNV, namely samples from Central Kalimantan and East Java. The test results were confirmed and reinforced by other supporting factors that influence the spread or occurrence of IMNV disease infection in the sample's region of origin. This study highlights the importance of routine IMNV surveillance using sensitive molecular methods to control disease spread and protect the shrimp aquaculture industry in Indonesia.